Optimizing Tomato Yield in Saline-Sodic Soils With Gypsum and Mulching Techniques Near Lake Abaya, Ethiopia - Birara Gebeyhu Reta; Woinshet Habite (Applied and Environmental Soil Science)
The productivity of tomato fruit on the western shore of Lake Abaya in Ethiopia was severely hindered by saline-sodic damage. This study aimed to assess the impact of applying gypsum and adopting soil mulching agricultural technology to improve the issues of salt-affected soil in the region. The treatments consisted of a control group (T1), mulching (T2), gypsum application (T3), and a combination of gypsum (half level) and mulching (T4). Application rates of gypsum and straw mulching were 14.5 and 15 tons/ha, respectively. The mean total seasonal crop water consumptions of tomatoes were 378 mm (non-mulching) and 333.02 mm (mulching). Straw mulching saved an average of 13.2% of soil water compared with non-mulching treatments. At the end of the growing season, exchangeable sodium percentage was decreased by 42.3% (T2), 38.1% (T3), and 43.8% (T4) compared with control T1. The pH levels at the experimental site experienced reductions of 15.1% (T2), 1.1% (T3), and 14% (T4) compared with T1. The soil electric conductivity of the soil at the end of the tomato growing period was decreased by 59.6% (T2), 19.2% (T3), and 46.2% (T4). The average land productivity of tomatoes in the current study was 14.9c tons/ha (T1), 16.2b tons/ha (T2), 15.0c tons/ha (T3), and 18.6a tons/ha (T4). The average water productivity of tomatoes in the current study was 5.5c kg/m3 (T1), 7.2b kg/m3 (T2), 6.5c kg/m3 (T3), and 7.8a kg/m3 (T4). The benefit-cost ratios for T1, T2, T3, and T4 were 1.67, 2.2, 1.78, and 2.4, respectively. The optimal strategy for mitigating saline-sodic soil and ensuring sustainable tomato production involves applying gypsum at half the recommended level along with implementing straw mulching.